2018
DOI: 10.1111/manc.12225
|View full text |Cite
|
Sign up to set email alerts
|

Labour Unions and Firm Productivity: Evidence from China

Abstract: This study investigates the effect of labour unions on productivity across various types of firm ownership in China. Using a panel dataset of Chinese manufacturing firms covering 2004–2007 and employing propensity score matching techniques, we find that unions have a negative impact on labour productivity and total factor productivity. From a dynamic viewpoint, unionisation has an initially positive or nonsignificant association with productivity, but then has a significant negative effect in subsequent years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Recent research in China have identified negative impact of degree of unionization on productivity (Yang & Tsou, 2018). Despite similarity between China and India on multiple parameters such as overall population; presence of large state-owned enterprises and comparatively recent changes in economic policy, we have found evidence for positive association between firm productivity (measured as sales per employee and PAT per employee) and degree of unionization in the context of India which is intriguing and counterintuitive.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Recent research in China have identified negative impact of degree of unionization on productivity (Yang & Tsou, 2018). Despite similarity between China and India on multiple parameters such as overall population; presence of large state-owned enterprises and comparatively recent changes in economic policy, we have found evidence for positive association between firm productivity (measured as sales per employee and PAT per employee) and degree of unionization in the context of India which is intriguing and counterintuitive.…”
Section: Discussioncontrasting
confidence: 62%
“…Interestingly, research in same country has also led to contradictory findings. For example, positive (negative) relationship between unionization and employee-level productivity has been identified in Japan, Germany, and China by Morikawa (2010), Fitzroy and Kraft (1987) and Budd, Chi, Wang, and Xie (2014) (Brunello (1992), Schnabel (1991) and Yang and Tsou (2018) and Bradley, Kim, and Tianc (2016) (both in China).…”
Section: Germane Literaturementioning
confidence: 99%
“…The impact of unionism on productivity was investigated heavily by multiple researchers with varying conclusions. Some researchers reported the unionization positive impacts on productivity (Freeman and Medoff, 1983; Allen,1984; Gao et al , 2020), while other researcher either reported the opposite case (Yang and Tsou, 2018) or found that the impacts of unions on productivity may be country-specific, industry-specific, and even time-specific (Doucouliagos and Laroche, 2003). Similarly, conflicting conclusions in the literature were made about the unionization cost impact.…”
Section: Introductionmentioning
confidence: 99%
“…From the economic perspective, some researchers have found that a union positively impacts on enterprise productivity (Doucouliagos et al, 2018;Fang et al, 2019;Freeman and Medoff, 1984). Conversely, two studies analyzing Chinese data indicate that unions are not conducive to improving enterprise productivity (Liu et al, 2013;Yang and Tsou, 2018). These arguments indicate that unions may indirectly contribute to improving corporation performance by first enhancing individual employee performance.…”
Section: Introductionmentioning
confidence: 99%